2016
DOI: 10.1371/journal.pone.0162684
|View full text |Cite
|
Sign up to set email alerts
|

Micro and Macroscale Drivers of Nutrient Concentrations in Urban Streams in South, Central and North America

Abstract: Global metrics of land cover and land use provide a fundamental basis to examine the spatial variability of human-induced impacts on freshwater ecosystems. However, microscale processes and site specific conditions related to bank vegetation, pollution sources, adjacent land use and water uses can have important influences on ecosystem conditions, in particular in smaller tributary rivers. Compared to larger order rivers, these low-order streams and rivers are more numerous, yet often under-monitored. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…It is observed that approaches that did not address environmental challenges in a holistic manner produced rebound effects with implications for degradation of water and soil resources [29]. In Brazil, land use has been affecting raw surface-water quality for drinking supply [30], and there is eutrophication of local aquatic systems [31,32].…”
Section: Incidence and Impact Of Eutrophication: Some Evidencementioning
confidence: 99%
“…It is observed that approaches that did not address environmental challenges in a holistic manner produced rebound effects with implications for degradation of water and soil resources [29]. In Brazil, land use has been affecting raw surface-water quality for drinking supply [30], and there is eutrophication of local aquatic systems [31,32].…”
Section: Incidence and Impact Of Eutrophication: Some Evidencementioning
confidence: 99%
“…We used data on the participation of 7413 FWW citizen scientists from 13 countries who were trained to participate in the HWP. Participants used a standardized FWW method with the addition of 1 of 25 protocols that varied in the technologies used, site selection procedures, sampling regularity, and degree of coordination (see Loiselle et al 2016 andThornhill et al 2018 for further details). Participants were recruited through an internal promotion campaign within the HSBC bank.…”
Section: Methodsmentioning
confidence: 99%
“…Citizens' role in some of these project is, for example: -Recognition of images (e.g. taken with robot boat) to verify whether the wild life exists or not in the water (BrooklynAtlantis, 2012); -Water sample collection for localization of clean water habitats in urban landscapes (McGoff, et al, 2017); -Micro and macroscale nutrient concentration monitoring (Loiselle, et al, 2016;Yuchao, et al, 2017); -Quantification of anthropogenic litter on lake beaches (Vincent, et al, 2017); -Water turbidity and water clarity monitoring [ (Leeuw & Boss, 2018); (Seafarers, et al, 2017)].…”
Section: Figure 2: Number Of Published Papers Related To Water Qualitmentioning
confidence: 99%